The Phenomenon of Alchemy in the Temporal, Spatial and Mental Dimensions of the Old World - Kostiantyn Rodyhin; Mykhailo Rodyhin (Cхід, 2013)
The paper deals with the phenomenon of alchemy in the temporal, spatial and mental dimensions of the Old World. The comparative analysis of the typical features of alchemy reveals the essential unity of this phenomenon in the West and the East. The authors consider the polycentric model of the origin of alchemy to be probable. Alchemy in all the variety of manifestations is focused on obtaining an unlimited resource - material, temporal, creative etc. The specifics of the manifestations of alchemy are caused by difference between the deep collective settings - introverted position of the East and extraverted position of the West. In the Western alchemy, the collision between the external orientation of ideas and the mystico-esoteric nature of tradition causes the breakthrough of "hermetic sealing" of the phenomenon.